An Exploratory Case Study of One Early Career Teacher’s Evolving Teaching Practice in Northern Canada - Murray-Orr, Anne; Mitton-Kukner, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2017)
This paper focuses upon the case of one early career teacher, Don, a participant in a longitudinal study examining the transfer of learning about literacy practices from pre-service teacher education to the classrooms of secondary content area teachers. We followed Don from his B. Ed. program into his first two years of teaching in an Indigenous community in northern Canada, with a focus on how his pedagogical content knowledge and his culturally relevant pedagogical practices developed. This case traces Don’s journey from his goals and plans at the end of his teacher education program, through his feelings of uncertainty near the end of his first year of teaching, to his growing confidence in his second year of teaching.